2016
DOI: 10.1007/s10911-016-9358-3
|View full text |Cite
|
Sign up to set email alerts
|

p120-Catenin Is Critical for the Development of Invasive Lobular Carcinoma in Mice

Abstract: Loss of E-cadherin expression is causal to the development of invasive lobular breast carcinoma (ILC). E-cadherin loss leads to dismantling of the adherens junction and subsequent translocation of p120-catenin (p120) to the cytosol and nucleus. Although p120 is critical for the metastatic potential of ILC through the regulation of Rock-dependent anoikis resistance, it remains unknown whether p120 also contributes to ILC development. Using genetically engineered mouse models with mammary gland-specific inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Inactivation of the AJ as a whole is not the determining factor for the formation of lobular breast cancer. Whereas somatic ablation of E‐cadherin in the mammary gland results in metastatic mouse ILC , inactivation of the AJ through p120 loss induces the formation of invasive high‐grade and basal‐like IDC . It appears that ILC may uniquely depend on Rho/Rock‐driven actin remodeling, given that p120 null mammary carcinoma cells and IDC‐derived human tumor cell lines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the AJ as a whole is not the determining factor for the formation of lobular breast cancer. Whereas somatic ablation of E‐cadherin in the mammary gland results in metastatic mouse ILC , inactivation of the AJ through p120 loss induces the formation of invasive high‐grade and basal‐like IDC . It appears that ILC may uniquely depend on Rho/Rock‐driven actin remodeling, given that p120 null mammary carcinoma cells and IDC‐derived human tumor cell lines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant genetically engineered mouse models carrying various mutations in conjunction with CDH1 deletion, mimic different aspects of the disease (Derksen et al , 2006; Boelens et al , 2016; Tenhagen et al , 2016; An et al , 2018) and of particular subtypes, such as the classic (Boelens et al , 2016) or inflammatory ILC (An et al , 2018). However, these models lack the high ER and PR expression characteristic of the human disease and are of limited value in mimicking the metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, when inactivated in conjunction with p53, loss of p120 did not result in tumors with an ILC-like morphology [132]. Moreover, deletion of p120 catenin in addition to E-cadherin and p53 did not accelerate tumor formation, and the morphology of these triple-knockout tumors was predominantly sarcomatoid [133]. This indicated that cytoplasmic p120 catenin is required for the development of ILC in mice.…”
Section: Genetically Engineered Ilc Mouse Modelsmentioning
confidence: 95%